ANALYSIS OF BOGOR REGENCY REGIONAL REGULATION NUMBER 5 OF 2015 CONCERNING PROTECTION OF WOMEN AND CHILDREN FROM ACTS OF VIOLENCE - Azzahra, Melani; Nuwati (Fakultas Hukum Universitas Djuanda, 2024)
Violence has a negative impact on health, social welfare and economic stability. From a health perspective, this leads to physical and mental injuries, disabilities and other related health problems. Violence against women and children includes acts that cause physical, psychological, sexual suffering, neglect and exploitation. This form of violence is an important topic of debate in various circles. Women and children are often victims of various forms of violence, including discrimination. The Policy for the Protection of Women and Children from Acts of Violence is an effort made by the Bogor Regency Government to specifically provide services to victims of violence against women. and child. The aim of this research is to find out legal protection for women and children. This research uses a sociological juridical legal approach and the specifications in this research include analytical descriptive. The results obtained in this research show that the Government has carried out its role ideologically, through the existence of service institutions which functionally are medical, legal and psychosocial service institutions for victims of violence. However, there are still many improvements needed to reduce the level of violence against women and children that occurs in Bogor Regency considering that the number of cases of violence is still experiencing an increasing trend to date.